Thermal comfort and occupant behaviour in office buildings in south-east China - Wu, Jindong (2015)
Natural ventilation is a passive cooling method that has significant potential to reduce building energy consumption and to positively contribute to indoor environmental conditions. Because the window is an important element in naturally ventilated buildings, it can be used to adjust indoor air flow. However, lack of knowledge about occupants‘ window control behaviour and how this relates to different window typology would result in discrepancy between actual and proposed building performance. And also, limit the potential of natural ventilation in the building. This thesis explores the relationship between indoor air velocity, occupants‘ window control behaviour and window design.